2008
DOI: 10.1007/s00381-007-0554-8
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent intracranial insertion of a soft rubber tube in a patient with Treacher-Collins syndrome: case report and review of literature

Abstract: The potential implications of an inadvertent foreign body penetration into the intracranial compartment in such a rare event are discussed and the relevant literature is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In general, patients who have facial trauma, nasal injury, or abnormal nasal anatomy that precludes nasal access are candidates for oroenteric tubes (4). There have been published data that indicate that patients with nasal airway intubation have more episodes of sinusitis than patients with oral airway intubation (5).…”
Section: Introductionmentioning
confidence: 99%
“…In general, patients who have facial trauma, nasal injury, or abnormal nasal anatomy that precludes nasal access are candidates for oroenteric tubes (4). There have been published data that indicate that patients with nasal airway intubation have more episodes of sinusitis than patients with oral airway intubation (5).…”
Section: Introductionmentioning
confidence: 99%
“…10 However, anterior skull base defects in patients with BCA and congenital anomalies have been reported that increase the risk of surgical repair. 9 15 CHARGE syndrome can include craniofacial abnormalities that can increase the risk of skull base injury. One CHARGE patient in this series had an absent crista galli and membranous nasal roof without encephalocele.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, skull base injury both and immediately following CA repair has been described. [8][9][10] Recent studies have shown an increase in clival abnormalities including clival clefts and clival shortening in CHARGE patients. 11,12 Additionally, BCA has been associated with skull base defects including dehiscence, nasal dermoids, and encephaloceles.…”
Section: Introductionmentioning
confidence: 99%
“…They often have abnormal skull bases, with defects into the cranial cavity and intracranial injury following surgery has been reported [32,33]. They often have abnormal skull bases, with defects into the cranial cavity and intracranial injury following surgery has been reported [32,33].…”
Section: Craniofacial Abnormalitiesmentioning
confidence: 99%